Serological profile of febrile rash in patients at a tertiary care hospital in Telangana - Dr. Afroze Sultana; Dr. M.L. Kavitha Latha (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Evaluating the patients who presents with fever and rash can be challenging because the differential diagnosis is extensive and includes minor and life-threatening illnesses. Materials & Methods: A total of 300 patients with provisional diagnosis of acute febrile illness were evaluated during the period of August 2016 to July 2017 at Sir Ronald Ross Institute of Tropical and Communicable Diseases, Nallakunta, Hyderabad. All the clinically suspected cases of febrile rash were subjected for serological study. Results: Most commonly affected age group is 14-40 years. Fever is the most common symptom. NS1ag was detected in 44.7% of cases. Secondary dengue infection is 12.3%. IgM is positive in 57.1% of chikungunya cases. The chicken pox IgM positivity was reported in 80% of cases. About 82.8% of measles serologically confirmed cases. Conclusion: Diagnosis can be established serologically in 63.6% of cases there by emphasizing the need for Clinico-serological correlation of rashes. Acute febrile illness comprises infection due to malaria, influenza, leptospirosis, scrub typhus, typhoid fever, and dengue, of which some infections necessitate specific treatment. As antibiotics will be required to treat bacterial diseases, knowing the viral etiology will help in avoiding unnecessary administration of antibiotics.